Efficient malic acid production from glycerol with Ustilago trichophora TZ1. Issue 1 (December 2016) - Zambanini, Thiemo; Sarikaya, Eda; Kleineberg, Wiebke; Buescher, Joerg; Meurer, Guido; Wierckx, Nick; Blank, Lars
Abstract Background The large surplus of crude glycerol, as main low-value waste stream in biodiesel production, has led to the investigation of new possibilities for the production of value-added chemicals from this feedstock. New and efficient (bio-) catalysts are needed that are able to convert glycerol to versatile chemical building blocks. This would contribute to further develop away from a mainly petroleum based, to a sustainable, bio-based industry. One promising group of discussed building block chemicals are dicarbonic acids. Results Here, we report the efficient synthesis of malate from glycerol usingUstilago trichophora RK089, which was identified in a screening of 74 Ustilaginaceae. For economically feasible production that can compete with existing processes, a high productivity is required. By adaptive laboratory evolution, the growth and production rate were increased by 2.5- and 6.6-fold, respectively. Further medium optimization increased the final titer, yield, and overall production rate to 196 g L−1, 0.82 gmal ggly −1, and 0.39 g L−1 h−1, respectively. Conclusions This titer is the highest reported for microbial malate production, makingU. trichophora TZ1 a promising microbial production host for malate from crude glycerol, especially since it is not genetically engineered. Since this production process starts from an industrial waste stream as substrate and yields an interesting platform chemical, which can be used to replace petro-chemicals, it greatly contributes to a sustainable bio-economy.